Development of Student Worksheet Based on Discovery Learning Models and Circular Motion Practicum Tools Based on Digital Technology: Design, Validity, and Practicality - Novita Virmani (IJER (Indonesian Journal of Educational Research), 2020)
This article discusses the student worksheet and circular motion practicum tools based on digital technology. Due to the unavailability of both student worksheet and circular motion practicum tool that matched the student’s characteristics and 2013 curriculum demands, this article proved the validity and practicality of student worksheets based on discovery learning models and circular motion of practicum tools in learning. The development model used was a 4-D model consisting of define, design, develop, and disseminate stages. The data was obtained by using a validity, practicality and effectiveness questionnaire validated by the validators. Five validators validated student worksheet based in the discovery learning and one validator validated the circular motion practicum tool. The result showed that the student worksheet based on the discovery learning model and the circular motion practicum tool was valid and parctical.